Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Harga Terhadap Kepuasan Pelanggan PAM PT. Watertech Estate Cikarang - Bakti, Rizal; Perkasa, Edu Mantara (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
The type of research carried out using a quantitative approach with the research method used is survey research using questionnaires as a means of collecting basic data. The data analysis model used is multiple linear regression analysis. To determine the sample to be used, the researcher used incidental sampling techniques. The regression test results show that the Adjusted R Square value is 0.491 or if it uses a percentage of 49.1%. This means that the independent variable or independent variable, namely product quality, service quality, and price together (simultaneously) affects the dependent variable or dependent variable, namely customer satisfaction by 49.1% while the remaining 50.9% is influenced by other variables that are not included in this study. While the results of the F test show that simultaneously the variable quality product, service quality, and price have a positive and significant effect on the variable customer satisfaction with the results of the calculated F value of 32.855 greater than the F table which is 2.700. The results of the t-test show that the product quality variable gets at a value of 2.467, the service quality gets at a count of 3.368 and the price gets a value of 4.088 t where the t table value is 1.985. So partially the product quality, service quality, and price variables have a positive and significant effect on customer satisfaction PT. Watertech Estate Cikarang.